2015
DOI: 10.1515/acve-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Concentrations of Acute Phase Proteins in Calves during the first Month of Life / Promene Koncentracije Proteina Akutne Faze Tokom Prvog Meseca Života Teladi

Abstract: The objective of this study was to describe the physiological changes in the concentrations of acute phase proteins (APPs) in calves during the fi rst month of life, including pre-, postcolostral and milk feeding period. Seven clinically healthy calves were used in this study. Calves received colostrum and whole milk from their dams. The fi rst blood sampling was performed before colostrum intake (day 0) and then at 1, 2, 7, 14 and 30 days of age. Blood serum was analyzed for the concentrations of haptoglobin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
3
13
1
2
Order By: Relevance
“…Results of albumin concentration corroborate those of Tothova et al (2015), who observed decreasing concentrations of albumin during the first week, followed by increasing concentrations until 30 days of age, when experimental period ended. Glucose concentrations were expected to decrease and those of BHBA to increase as starter intake increases and rumen develops.…”
Section: Discussionsupporting
confidence: 87%
“…Results of albumin concentration corroborate those of Tothova et al (2015), who observed decreasing concentrations of albumin during the first week, followed by increasing concentrations until 30 days of age, when experimental period ended. Glucose concentrations were expected to decrease and those of BHBA to increase as starter intake increases and rumen develops.…”
Section: Discussionsupporting
confidence: 87%
“…In cases of viral (foot-and-mouth disease and bovine respiratory syncytial virus) or parasitic (Eimeria and Cryptosporidium) infections, APP concentrations can increase in domestic ruminants' blood serum (Orro et al, 2011;Pourjafar et al, 2011;Stenfeldt et al, 2011;Lassen et al, 2015). In neonatal calves, APPs go through significant changes during first 2 to 3 weeks of life (Orro et al, 2008;Tóthová et al, 2015), suggesting that APPs have a role in the adaptation of neonate calves to the new environment. In reindeer calves, lambs, and beef calves, high concentrations of SAA measured in the second week of life have been associated with lower weight gain recorded many months later (Orro et al, 2006;Peetsalu et al, 2013;Seppä-Lassila et al, 2015, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Este processo de adaptação foi utilizado para justificar aumentos na concentração de PFA em bezerros e caprinos nos primeiros meses de vida (Tóthová et al, 2015;Ulutas et al, 2017). Por outro lado, o colostro pode exercer influência sobre a concentração sérica de PFA no período neonatal (Tóthová et al, 2015). O efeito precoce de doenças não deve ser descartado, já que o status de higidez nem sempre reflete em concentrações baixas de PFA.…”
Section: Resultsunclassified
“…Apesar da promessa de grande aplicabilidade no diagnóstico, prognóstico e monitoramento da saúde animal, o uso das PFA na rotina laboratorial depende do fornecimento de valores basais em diferentes condições fisiológicas para serem usadas como de normalidade ou mesmo de referência (Eckersall et al, 2000). O estudo do comportamento das PFA é fundamental para a compreensão das alterações ao longo do desenvolvimento dos animais, visto que em bezerros foi possível observar aumentos na concentração sérica de PFA nos primeiros dias de vida (Tóthová et al, 2015), assim como em cabritos (Ulutas et al, 2017).…”
Section: Introductionunclassified